Building an Environmentally Caring Community Through Dasawisma - Fitra Hadi Khaz; Refdi Refdi; Muhammad Arya Wijaya; Novier Jorgi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Household environmental problems such as poor waste management, the practice of burning waste, and limited use of home yards remain major challenges in creating clean and healthy residential areas. Dasawisma, as the smallest unit within the PKK structure, holds a strategic role in fostering environmental awareness and pro-environmental behavior at the family level. This Community Service Program (PkM) aims to build an environmentally caring community through strengthening the role of Dasawisma, improving members' knowledge, and encouraging new habits in household environmental management. The method used a participatory approach consisting of problem identification, interactive counseling sessions, hands-on practice in waste management and yard utilization, and field mentoring. The results indicate an increase in members' understanding of environmental issues, behavioral changes in sorting organic and inorganic waste, simple composting practices, and the cultivation of plants in home yards. In addition, collective awareness and the emergence of local leaders helped sustain the environmental movement within the community. This program demonstrates that strengthening Dasawisma is an effective family-based empowerment strategy to support social transformation toward a cleaner, healthier, and more sustainable environment.